PROBLEM-BASED LEARNING TECHNOLOGY IN NATURAL SCIENCES - Mirzabekova, Gumshagul Khujabekovna (SCIENCE and SOCIETY, 2026)
The article highlights the methodological foundations and practical significance of using problem-based learning technology in teaching natural sciences in primary school. The author analyzes how creating problem situations during the lesson helps to increase students’ logical thinking and cognitive activity. The research results show that the problem-based approach is superior to traditional methods in developing students’ independent research and inquiry skills.